Shallow meritocracy - Peter Andre (Leibniz Institute for Financial Research SAFE, 2023)
Meritocracies aspire to reward hard work and promise not to judge individuals by the circumstances into which they were born. However, circumstances often shape the choice to work hard. I show that people's merit judgments are "shallow" and insensitive to this effect. They hold others responsible for their choices, even if these choices have been shaped by unequal circumstances. In an experiment, US participants judge how much money workers deserve for the effort they exert. Unequal circumstances disadvantage some workers and discourage them from working hard. Nonetheless, participants reward the effort of disadvantaged and advantaged workers identically, regardless of the circumstances under which choices are made. For some participants, this reflects their fundamental view regarding fair rewards. For others, the neglect results from the uncertain counterfactual. They understand that circumstances shape choices but do not correct for this because the counterfactual-what would have happened under equal circumstances-remains uncertain.
Keywords: C91; D63; D91; H23; 330; Meritocracy; fairness; responsibility; attitudes towards inequality; redistribution; social preferences; inference; uncertainty; counterfactual thinking